PENGARUH KUALITAS SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI DAN PENGAWASAN KEUANGAN TERHADAP PELAPORAN KEUANGAN PEMERINTAH DAERAH KEPULAUAN SELAYAR - Fina Diana; Nurmiati Nurmiati; Nur Hadiwijaya (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
This study aims to determine the effect of human resources, information technology, and financial supervision of the financial reporting information of the Regional Government of Selayar Islands Regency. The analytical method used in this research is quantitative analysis method, that is analysis using numbers and statistic calculation to analyze a hypothesis and need some analysis tool that is: (1. Validas and reability of research data, 2. Multiple regression analysis). The result of the research found that Human Resource and Financial Supervision have positive and significant influence to Local Government Financial Reporting of Selayar Islands Regency. While Information Technology has no effect on Financial Deposit with Rule of Regression Squared (R2) is 0,923, this means 92,3% change variation of all variables can be explained simultaneously by human resource variable and financial control. The rest of 7.7% is determined by variables or other factors from outside the model.